Synthesis, Crystal Structures and Xanthine Oxidase Inhibitory Activity of Benzohydrazone Compounds - Zhang1, Wei-Ming; Sheng2, Gui-Hua; You3, Zhonglu (Asian Journal of Chemistry, 2014)
A series of three benzohydrazone compounds, 2N'-(5-hydroxy-2-nitrobenzylidene)-4- methylbenzohydrazide (1), N'-(5-chloro-2-hydroxybenzylidene)-3-methylbenzohydrazide (2) and N'-(2,4-dichlorobenzylidene)-3-methylbenzohydrazide (3), were prepared and structurally characterized by elemental analysis, IR spectra and single crystal X-ray determination. Xanthine oxidase inhibitory activities of the compounds were studied. Among the compounds, N'-(5-hydroxy-2-nitrobenzylidene)-4-methylbenzohydrazide (1) shows the most effective activity with IC50 value of 15.2 ± 2.3 μM. Docking simulation was performed to insert the compound into the crystal structure of xanthine oxidase at the active site to investigate the probable binding modes.